Relationship Between Body Mass Index and Intraocular Pressure in Men and Women: A Population-based Study. Issue 5 (May 2016) - Cohen, Eytan; Kramer, Michal; Shochat, Tzippy; Goldberg, Elad; Garty, Moshe; Krause, Ilan
Abstract : Purpose: To assess the possibility of a relationship between body mass index (BMI) and intraocular pressure (IOP) in both men and women. Materials and Methods: A retrospective cross-sectional analysis of a database from a screening center in Israel which assessed 18, 575 subjects, within an age range 20 to 80 years. Results: The mean (±SD) age of the study sample was 46 (±10) years, 68% were men. A positive linear correlation was found between BMI and IOP for both men and women ( r =0.166, P <0.0001 in men and r =0.202, P <0.0001 in women). Mean (95% confidence interval) IOP in subjects with BMI<25 kg/m 2 was 12.8 mm Hg (range, 12.7 to 12.9 mm Hg) and increased significantly to 13.4 (range, 13.3 to 13.5 mm Hg); 13.9 mm Hg (range, 13.8 to14.0 mm Hg), and 14.3 mm Hg (range, 14.1 to 14.5 mm Hg) for BMI subcategories 25 to 29.9, 30 to 35, and >35 kg/m 2, respectively ( P <0.0001). These differences remained significant after multivariate adjustment for age, hypertension, and diabetes mellitus ( P <0.0001). Similar multivariate adjustments showed that the coefficient factors for BMI (95% confidence interval) affecting IOP were 0.087 (range, 0.076 to 0.098) P <0.0001 and 0.070 (range, 0.058 to 0.082) P <0.0001 for men and women respectively, indicating that in men and women, the changes in IOP associated with a 10 kg/m 2 increase in BMI were 0.9 and 0.7 mm Hg, respectively. Subjects with abnormal BMI compared with subjects with normal BMI had increased odds ratio of having IOP≥18 mm Hg after adjusting for confounding factors ( P <0.001). Conclusions: This study shows that obesity is an independent risk factor for increasing IOP in both men and women. We consider this finding particularly pertinent in the context of the current obesity epidemic.